Pesantren Educational Institutions Amid the Currents of Global Change - Iskandar, Khusnan (Journal of Education and Religious Studies, 2023)
This study aimed to explore the roles and challenges faced by pesantren in responding to global changes. A literature review approach was utilized to gain a comprehensive understanding of this topic. Over the past few decades, global transformations, including advancements in information and communication technology, globalization, and rapid information flows, have significantly impacted various aspects of life, including education. As traditional Islamic educational institutions, pesantren are not immune to these changes. This study identified key roles pesantren play in adapting to and addressing global transformations while maintaining their traditional values. Various scholarly sources, including academic journals, books, research reports, and online articles, were analyzed to develop a comprehensive perspective on the opportunities and challenges pesantren face in this evolving landscape. The findings of this study are expected to provide valuable insights and recommendations for the future development of pesantren education in an era of continuous global change.